On the Development of the Image of a Monastery in Russian Art of the 14th–16th Centuries - Buzykina, Iuliia N. (Actual Problems of Theory and History of Art, 2016)
ОмфалиRussian art of the second half of the 14th century demonstrates significant interest towards monastic themes. During this period the first depictions of Blachernai monastery appear in early icons of Intercession.In the mid. 15th century, the iconography of Russian monasteries started to develop. Particularly, there is an image of the Holy Trinity Monastery, founded by St Sergius of Radonezh, depicted on the walls of the St Sergius Church in Novgorod (1459–1463), and the Church of the Miracle of the Archangel Michael at Chonae founded by St. Alexios, the bishop of Moscow, is depicted on the icon of St. Alexios with scenes of his life painted in the 1480s.In the 16th century, sights of Russian monasteries, depicted as churches surrounded by walls, sometimes with scenes of miracles, became subjects for icon-painting. Among them, we should mention the “House of Sts. Zosimas and Sabbatius” with views of the Solovetski Monastery. Architecture became the main content of the plot of those icons. Another interesting subject is the “House of St Sabbatius of Tver”, the subject that, however, never fully developed. It contains scenes from the Bible and the New Testament integrated into the space of monastery. They probably had in mind the so-called proskynetarion icons containing sights of Jerusalem and the Holy Land with scenes from the Holy Writ.The author underlines that the interest towards architecture of monasteries is a distinctive feature of Russian art. It can be tied with the fact that most of the Russian monasteries in the 16th century were coenobian, which in Russian climate meant a large number of buildings. Technical drawings, as well as views of the Holy Land, played an important role in generating such subjects.
Keywords: Medieval Russian art; Byzantine art; icon-painting; wall painting; book miniature; depictions of monasteries